Active solar collector located on roof ridge assisted Chinese solar greenhouse for thermal environment enhancement. Issue 4 (21st December 2022) - Hu, Yixin; Miao, Lili; Song, Lei; Li, Chenhao; Xiao, Jinxin; Wang, Hao; Cao, Yanfei; Sun, Guotao; Li, Jianming
ABSTRACT: Maximizing the use of solar energy to increase the indoor temperature of greenhouse is of great significance to the green and energy-saving intensive greenhouse production in China. In this study, an active solar heating system (ASHS) was developed and analyzed, consisting of five solar water heaters equipped with vacuum tube solar collectors, one heat storage tank and heating system including booster pump and heating pipes. During the day, the water was heated in the solar collectors and stored in tanks before being placed into circulation in the heating pipes to distribute the heat to the aerial and root zones of plants. To evaluate the performance of ASHS and the feasibility of practical application, climate and plant growth parameters were monitored in two Chinese Solar Greenhouses (CSGs) located in Yangling, China. Results revealed that under the operating condition with the flow rate of 5.4 L/min, the effective heat collection, average heat collection efficiency and energy-saving efficiency of ASHS were 1.9 MJ/(m 2 h), 64% and 84%, respectively. The coefficient of performance (COP) was between 4.5 and 6.2, and the payback period was 12.0 years. Furthermore, the results revealed that the ASHS successfully provided 76% of its annual heating needs, heated the CSG for 4 months and maintained the nocturnal temperature above 8 ℃. The actual application effect proved that it increased average indoor air temperature by 2.2 ℃ and substrate temperature by 3.3 ℃ in heated greenhouse. The growth rate of tomato plant height in the heated greenhouse was 0.7427 cm/d, greater than that in the unheated greenhouse (0.6 cm/d). The novel system proposed in this study adopting particular location enables the rise of the ambient and the substrate temperatures with lower energy consumption, improvement of the environmental conditions in CSG, and a more suitable growing environment for plants in the cold season.